Severe hemodynamic instability in a patient with suspected hepatoadrenal syndrome during liver transplantation -A case report- - Seong-Soo Choi; Jihion Yu; Young-Kug Kim; Gyu-Sam Hwang (Korean Journal of Anesthesiology, 2013)
Adrenal insufficiency, which is related to hemodynamic instability and increased mortality, has been reported in patients with advanced liver disease regardless of the presence of septic conditions. In this regard, the hepatoadrenal syndrome has been recently proposed as adrenal insufficiency in critically ill patients with liver disease. We describe here a 67-year-old female patient with hepatic failure and adrenal insufficiency. The patient showed stable vital signs and no evidence of sepsis preoperatively. Despite hydrocortisone replacement and inotropics administration, severe intraoperative hemodynamic instability was observed. Hydrocortisone administration was continued postoperatively, nevertheless inotropics could not be tapered. On postoperative day 11, the patient died due to pneumonia and septic shock. Hepatoadrenal syndrome may have played a key role in her severe hemodynamic fluctuation and poor outcome, reinforcing the importance of adrenal function in the liver transplantation surgery.